Heavy metals in seaweed: Implications for health benefits, risks, and safety regulations - Lori Huang; Ji-Young Lee; Young-Ki Park; Jaeeun Lee (Journal of Agriculture and Food Research)
Seaweed is widely recognized for its high nutrient content, including essential minerals, antioxidants, and other bioactive compounds. However, environmental factors can lead to heavy metal accumulation, particularly arsenic, cadmium, lead, and mercury, posing serious health risks such as carcinogenicity, neurotoxicity, and oxidative damage. This review summarizes the current knowledge of the prevalence of heavy metals in various seaweed species, explains how these metals are absorbed, distributed, and become toxic in humans, and evaluates the health risks associated with both short- and long-term consumption. Evidence shows that heavy metal contamination in seaweed is common, making excessive or prolonged intake potentially hazardous. Although seaweed has a beneficial nutrient profile, comprehensive seaweed-specific safety regulations are urgently needed to ensure consumer protection. Inconsistencies in current guidelines, underscore the need for stronger standards, routine monitoring, and expanded research to identify safe intake levels. Ultimately, while seaweed remains a valuable dietary resource, enforcing permissible limits on heavy metals and educating consumers can help ensure that its health advantages are not compromised by toxicological concerns.